Let George do it! - Foreman, George, 1949-; Manushkin, Fran.; Martin, Whitney, 1968- (New York : Simon & Schuster Books for Young Readers, 2005)
Five brothers named George, along with Mrs. George, get ready for Big George's birthday party.
Ages 4-8.
Keywords: Names, Personal -- Fiction; Parties -- Fiction; Birthdays -- Fiction